A framework for heuristic evaluation on Islamic websites - Mahmud, Murni; Md Tap, Abu Osman; Aliyu, Mansur (IIUM Press, 2011)

(untitled)
Islamic Websites are an important means of communicating the Islamic messages. lt delivers Islamic teaching to the Ummah. Evaluation of Islamic websites posts great challenges as the websites must reflect the meaning of Islamic way of life. The content must be accurate, correct, credible and true with recognised references. As such, the problem addressed in this study is the lack of suitable definition and measures for evaluating the quality of Islamic websites. This study aims to identify and examine both design and content features that relates to Islamic websites. This study has evaluated fifty (50) selected Islamic websites. Nine (9) design features have been identified which are: navigation, interactivity, and attractiveness) and content features (i.e. legitimacy, objectivity, authority, relevance, credibility, and reliability). A heuristic evaluation method (Sutcliffe, 2002) and procedure (Agarwal & Venkatesh, 2002) involving a single-user was used (Mahmud et aI., 2010). The findings suggest that Islamic websites demonstrates good quality on their design and content features. The findings also indicate that the overall Islamic website's quality varied significantly between different Islamic websites. In addition, the results suggest that new additional features influence the overall quality of Islamic websites. Finally, the authors, propose a working definition and an enhanced framework for evaluating the quality of Islamic websites. 226